Gender differences in neuropsychological outcomes following sports-related concussion: a systematic review - Fuhrmanna, K.; Spittleb, M.; Lindsay, R. (Journal of Science and Medicine in Sport, 2024)
Introduction: Sport-related concussions (SRC) constitute a significant risk to athletes globally, with growing concern about the ramifications of SRC. Implications of SRC include physical, emotional, and neuropsychological symptoms that can impair function, in some cases for months. There has been a growing body of evidence to suggest that the symptomology of SRC differs between female and male athletes, with females seen to experience a greater incidence, severity, and number of concussion symptoms. This systematic review aims to identify if there are gender differences in neuropsychological outcomes of SRC. Methods: A PRISMA-P approach was utilised, with Medline, APA PsychInfo, Web of Science and SportDISCUS databases searched using key terms in June 2023 with a final search completed in September 2023. A quality and risk of bias assessment was conducted using the National Institutes of Health study quality assessment tools for cohort, observational and cross-sectional study designs. Results: The systematic review included 18 studies (n = 4995). A total of 2467 athletes were included across studies, with 39% being female (Male = 1494; Female = 973). Data synthesised from these studies revealed gender differences in visual memory (n = 5), verbal memory (n = 3), and reaction time (n = 3). With the exception of one study focused on verbal memory, all significant gender differences revealed females performed worse relative to males following a SRC. No clear gender differences were observed in motor processing speed. Risk-of-bias assessment indicated a bias toward male-focused research. Discussion: The aim of this systematic review was to investigate whether any gender differences existed in neuropsychological outcomes (memory, reaction time and motor processing speed) in athletes who have a history of sport-related concussions. The results suggested a trend toward gender differences in reaction time, and visual and verbal memory. These findings extend on previous reviews, highlighting the potential for females to experience greater deficits in specific neuropsychological outcomes following an SRC. Furthermore, a key difference with this review was that inclusion criteria required studies to include baseline testing using a known concussion measure, the most common in the included articles being the ImPACT measure (n = 13). This criterion meant most studies were based in North America. Of these studies, all but one consisted of high school and college participants. This resulted in participants across studies being between 10-25 years old, limiting the generalisability of findings to older athletes. Impact/Application to the field: Further research examining the neuropsychological outcomes of concussion in adult populations with balanced gender samples is needed to determine the extent to which gender differences exist in neuropsychological outcome of concussion. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.